Bitpipe vs. service: Why do pure service providers outperform fully integrated operators? - Nico Grove; Oliver Baumann (International Telecommunications Society (ITS), 2011)
With the emergence of pure internet-based service providers, the business landscape of fully integrated telecommunications providers - industry incumbents that provide services on their own infrastructure - has changed massively. While various pure service providers exhibit successful business models and high performance, the services offered by the integrated telecommunication firms are not able to compete on neither price nor user experience. To shed light on this issue, we build upon work that has applied a complex systems perspective on performance - how firms manage to configure a large set of interdependent activities affects the performance of the overall activity system. We develop a simulation model to illustrate the effects of a) configuring only interdependent service-related activities, while building on an existing (external) infrastructure, and b) configuring both infrastructure-related and service-related activities at the same time. Our results point to a mechanism that helps explain the underperformance of the fully integrated operators. Pure service providers can improve the performance of their services speedily, as they can focus on optimizing only the service-related activities and adapting them to an existing infrastructure. Fully integrated operators, in contrast, will likely be concerned with both infrastructure and service components, taking into account also the interdependencies between these two domains. While this approach can help reap synergy effects and yield a performance advantage in the long run, it requires more time and results in a lower performance in the short run. Put differently, the objective of the integrated operators to integrate their bitpipe and service business puts these firms at a disadvantage when compared to their specialized competitors. We illustrate this mechanism with two case studies that show how fully integrated operators adapted their infrastructure in response to their service activities, which in return triggered further adaptations and coordination effort.
Keywords: 330; Telecommunication industry; complex systems; organizational search